MODELS OF WAQFFUNDRAISING MANAGEMENTIN INDONESIA - Miftahul Huda (IAIN Ponorogo, 2019)
AbstractNowadays, strengthening the capacity of nazir is very essential in gettingbenefits in terms of self-reliance and empowerment of mauquf alaih. One of its attempts israising fund as an advance of the improvement assets and waqf potential management.Therefore, this paper aims to investigate the uniqueness of waqf management in the viewpointof fundraising from three Nazir, namely, Hasyim Ashari Islamic boarding school TebuirengJombang, Foundation for Waqof Board and the Islamic University of Indonesia Yogyakarta andAl-Falah Social Fund Surabaya. This study employed multi case study from the perspective ofcomparative approach. The findings showed that there are three uniqueness of obtaining waqf,they are, tradition wisdom-based fundraising in Nazir Tebuireng Jombang, university-basedfundraising for community empowerment in Nazir UII Yogyakarta and the community-basedfundraising which focused on marginalized people in YDSF Surabaya. Referring to theexperiences of those three nazir above, there is diverse models in waqf fundraising. Thediversity is in the form of internalization fundraising, relationship fundraising, and integratedfundraising. Those three models lead to a series of holistic model of waqf fundraising in orderto keep the sustainable of waqf management, including the sustainability of nazir, assets,benefits, wakif and mauquf 'alaih. Abstrak Saat ini, penguatan kapasitas nazir sangat penting dalam pengembangankemandirian dan pemberdayaan mauquf alaih. Salah satu upayanya adalah mengumpulkan dana sebagai uang muka dari peningkatan aset dan potensi manajemen wakaf. Oleh karena itu, makalah ini bertujuan untuk menggali keunikan manajemen wakaf dalam sudut pandang penggalangan dana dari tiga Nazir, yaitu, UniversitasHasyim Ashari TebuirengJombang, Dewan Wakafdari Universitas Islam Indonesia Yogyakarta dan Dana Sosial Al-Falah Surabaya. Penelitian ini menggunakan studi multi kasus dari perspektif pendekatan komparatif. Temuan menunjukkan bahwa ada tiga keunikan dalam memperoleh wakaf, yaitu penggalangan dana berbasis tradisi kearifan di Nazir Tebuireng Jombang, pendanaan berbasis universitas untuk pemberdayaan masyarakat di Nazir UII Yogyakarta dan pendanaan berbasis masyarakat yang berfokus pada orang-orang pinggiran di YDSF Surabaya. Mengacu pada pengalaman ketiga nazir di atas, ada beragam model dalam penggalangan dana wakaf. Keanekaragaman itu dalam bentuk internalisasi, hubungandanintegrasipenggalangan dana. Ketiga model tersebut mengarah pada serangkaian model penggalangan dana wakafholistik dalam rangka mewujudkan keberlanjutan pengelolaan wakaf, termasuk keberlanjutan nazir, aset, manfaat, wakif dan mauquf 'alaih.